Conflict and Organization Studies. Issue 10 (October 2019) - Contu, Alessia
What is the relation between conflict and organization studies? Is conflict theorized today and, if so, how? I look first at what students of management are taught about organizational conflict – the knowledge imparted to them, its assumptions and ethico-political consequences. By reactivating Mary Follett's insight of conflict as 'differences in the world' I consider more broadly how organization studies, with its different theoretical apparatuses, treats conflict and in so doing participates in the co-constitution of the social order: what it means to work, to organize and to live specific ways of life. Organization studies attempts to domesticate conflict by reference to a fundamental fantasy that modulates, controls and stabilizes differences. Harmonious fantasies in the 'functionalist perspective' and the 'behavioural theory of the firm' are discussed. Special attention is paid to the 'organizational economic perspective' with its economist fantasy for the part it has played in cementing our contemporary hegemonic market governance. At present, cracks in the market governance are becoming glaring and differences are emerging that the specific apparatus of conflict domestication is struggling to accommodate. I suggest that organizational theorists rethink the theorizing apparatus of organization studies, and consider taking on a form of theorizing called 'demiurgic theorizing'. This forwards a type of knowledge production that puts differences at centre stage and faces up to the contemporary conflict demands of our time with responsibility and accountability.